THE EFFECTIVENESS OF LOCAL CULTURE-BASED MATHEMATICS LEARNING IN IMPROVING THE NUMERACY LITERACY OF STUDENTS - Asriyati Nadjamuddin; Sarson W. Pomalato; Evi Hulukati; Tedy Machmud (JMIE (Journal of Madrasah Ibtidaiyah Education), 2025)
Students’ numeracy literacy remains a significant challenge in higher education, particularly for prospective elementary teachers who must apply mathematical concepts in real-life contexts. This study aimed to examine the effectiveness of Gorontalo culture-based mathematics learning in enhancing numeracy literacy among fifth-semester students in the Pendidikan Guru Madrasah Ibtidaiyah program at IAIN Sultan Amai Gorontalo. A one-group pretest–posttest experimental design was employed with 38 students, using validated essay tests to measure their ability to interpret quantitative information, solve contextual problems, and apply numerical reasoning. Data were analyzed using the Wilcoxon signed-rank test and N-Gain analysis. Results indicated a significant improvement in numeracy literacy, with mean scores increasing from 38.98 in the pretest to 77.82 in the posttest (Z = -5.374, p < 0.001). The mean N-Gain score of 0.64 reflected moderate effectiveness. The integration of specific Gorontalo cultural elements, including Karawo embroidery motifs, traditional house architecture (Dulohupa and Bandayo Poboide), and musical instruments (Polopalo and Gambus), helped students relate abstract geometric concepts to familiar contexts and increased engagement. In conclusion, Gorontalo culture-based mathematics learning is an effective and innovative approach to improve numeracy literacy while fostering cultural awareness among prospective teachers. This study highlights the value of integrating ethnomathematics in higher education to strengthen both mathematical competence and appreciation of local wisdom.